Rekomendasi Resep Masakan Berdasarkan Ketersediaan Bahan Masakan Menggunakan Metode N-Gram dan Cosine Similarity - Ratna Tri Utami; Yuita Arum Sari; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Cooking recipes are the guidelines of a housewife in making a dish. Many recipes that there are easy for housewives to cook. But the reality, there are still a lot of housewife who doesn't understood the compatibility between the composition of cooking materials with dishes to be made. So it takes innovation to facilitate the search for a recipe in accordance with the composition of the available ingredients. It can be included in a form of information retrieval system. N-gram and cosine similarity methods can be used to match the available ingredients with the recommended recipes. Excess cosine similarity method didnt affect by the short length of a text document, because it just calculated only the term value of each document. The N-gram method consists of 3 types of processes: unigram, bigram, trigram which are serves for word processing. In this research, a model for recommendation of relevant recipes using N-gram method and cosine similarity was developed. The tests performed were the measurement of similarity and threshold determination. The results obtained that the system succeeded in calculating the similarity with the value of cosine 0.9. The greater of the value so it closer to the recommendation of the recipe in accordance with the query. From the third results of the best N-gram process is unigram with a threshold value is greater than or equal to 90% and a recall value of 1 and precision 0,2. It can be concluded that unigram is the best N-gram method process to recommend the recipes based on the ingredient.